Systematic review of authentication techniques in banking applications in Latin America - Puma Herencia, Luis R. (2024)
Computer security, especially authentication in banking applications, has become a critical issue to ensure the integrity and confidentiality of users’ financial information. The current situation presents significant challenges, such as vulnerability to attacks, lack of strong authentication, and lack of cybersecurity coordination across the region. The objective is to provide a systematic review on the updated and comprehensive perspective on authentication security in banking applications in Latin America, identifying trends, gaps and research opportunities. The methodology used followed a clear approach, using the PICO strategy to formulate the research question. An exhaustive review was carried out on the studies, applying inclusion and exclusion criteria, and following PRISMA guidelines. Having 150 articles as a base quantity from 2019 to 2023, of which 20 articles were selected that met the criteria for inclusion in the systematic review. The results revealed various authentication techniques used in Latin American banking applications, such as microservices, biometrics, multi-factor authentication and tokenization. Multi-factor authentication proved to be the most secure, with an average success rate of 97.9%, on the other hand, knowledge factor authentication proved to be the least secure, with an average success rate of 58%. Trends show an increase in the use of biometrics and multi-factor authentication from 2019 to today. It is important to highlight the critical need for additional authentication systems to guarantee customer trust and the integrity of financial data in the region.